2008
DOI: 10.1111/j.1444-2906.2008.01663.x
|View full text |Cite
|
Sign up to set email alerts
|

Breeding experiments of hermatypic coralGalaxea fascicularis: partial reproductive isolation between colonies of different nematocyst types and enhancement of fertilization success by presence of parental colonies

Abstract: KEY WORDS: Cnidaria, coral reef, fertilization, mitochondrial DNA, reproductive barrier.The reef-building (hermatypic) corals build the structural foundation of coral reefs in tropical and subtropical zones, and form the trophic basis of coral reef ecosystems. 1 These corals are symbiotic complexes of the cnidarian host, mostly of the order Scleractinia, and dinoflagellate endosymbionts Symbiodinium spp. Most hermatypic corals form colonies, and the bulk of their bodies are made of rigid calcified skeletons. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
(13 reference statements)
1
7
0
Order By: Relevance
“…Abe et al. () reported that the seasons are not completely separated because they managed to conduct fertilization experiments between types. Therefore, a reproductive isolation may not be complete between mt‐L and mt‐S, which may have resulted from a recent evolutionary speciation process.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Abe et al. () reported that the seasons are not completely separated because they managed to conduct fertilization experiments between types. Therefore, a reproductive isolation may not be complete between mt‐L and mt‐S, which may have resulted from a recent evolutionary speciation process.…”
Section: Discussionmentioning
confidence: 99%
“…Although cross‐type hybrids occurred as a result of fertilization experiments between types (Abe et al. ), the incubation time (4–5 h) with higher sperm concentration appears to be longer than those that occur in nature (see Iguchi et al. ; Nozawa et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These features are also correlated with the length of the non-coding region between the mitochondrial genes, cytochrome b ( cyt b ) and NADH dehydrogenase subunit 2 ( nad 2 ) (mt-Long: soft colony type and nematocysts with wide capsules and long shafts; mt-Short: hard colony type and nematocysts with thin capsules and short shafts) [ 7 , 8 ]; therefore, these two types represent novel clades or species. Interestingly, gamete fertilization experiments revealed that these two types show partial reproductive isolation [ 9 ]. However, the reproductive barriers that separate these sympatric types and that cause their genetic differentiation are not obvious.…”
Section: Introductionmentioning
confidence: 99%